Sex determination and gonad maturation of humphead wrasse, cheilinus undulatus in captivity - Tan, Bee Ling (2019)
The aim in this present study was to identify the sex and gonad maturation of humphead wrasse, Cheilinus undu!atus in captivity based on body sizes and histological assessment. A total of 65 tails C undulatus broodfish were reared in 150 tonnes cylindrical fiber-reinforced plastic (FRP) tanks with water circulation system throughout six months. C undulatus were fed until satiation once daily, six times a week with prey fish (Sardine/la sp.) enriched with 0.1 ml pure cod liver oil and squid. Growth parameters and morphological measurement, such as presence of eyeline, shape of genital papillae and hump on head, of the c undulatus as well as observation on gonad maturation were carried out. This finding reveled in captivity, female of C undulatus (n=13) attained an average body weight of 2.78 kg and total length 47.10 cm meanwhile male of C undulatus attained larger body weight (14.62 kg) and total length exceeding size of female (89.30 cm). A total of 51 tails of C undulatus were not be identified sex with average body weight and total length were recorded as 2.75 kg and 45.90 cm, respectively. The length-weight relationship showed that C undulatus performed an isometric growth pattern (b = 2.9487) with condition factor of 0.23 and 0.24 for male and female, respectively. Morphologically, female was identified with the alleviation of the hump on its head and the visibility of eyeline behind its eyes which was not seen in male C undu!atus. Histological observation on gonad had confirmed the sex of the female of C undulatus with the presence of primary-growth stage oocytes (01), cortical-alveolus stage (02) and vitellogenic stage (03) was discovered in mature active female. On the other hand, only primary-growth stage oocytes (01) was detected in another sampled of female c undulatus. Unfortunately, no gametes were obtained from male and unknown sex of c undulatus for further examination. In conclusion, sex of C undulatus in captivity can be differentiated through body size and morphological features, thus brood fish management can be done effectively in future.